No encalço dos companheiros: militantes do Partido do Trabalhadores (PT) sob vigilância da Delegacia de Ordem Política e Social do Espírito Santo (DOPS/ES) – (1978-1985) - Rocha Junior, José Carlos (2014)
This research has two goals. First, it aims to retell and analyze important moments of performance of the Workers’ Party (PT) militants in Espirito Santo State from 1978, when many of its founders got into the busy context of great national strikes. At that time they also worked for the organization of the party concerning the labor opposition, base ecclesiastic communities and the neighborhood movements. Between 1980 and 1985, they were already formalized militants actively involved in the election campaigns of 1982 and 1985, in the demonstrations and strikes of 1983 and in the campaign for direct elections (called in Brazil “Diretas Já”) in 1984. Second, this study also aims to analyze the functioning of DOPS-ES (Political and Social Order Department of Espírito Santo). In order to reach both goals this research will employ as main source produced and-or apprehended materials and also specific bibliography. The defended hypotheses are: a) concerning the functioning of the DOPS-ES and the maintenance of the regime, it is supported that the apprehension of materials, the production, the handling and the diffusion of information among institutions and departments which formed the bureaucratic net of the repressive machine were essential for the maintenance of the authoritarian government; b) concerning the attention provided by the DOPS- ES for PT and its militants, it was verified that it is due to: first, the profile of the political police and their basic role; second, the still strong anti-communist paranoia and the results of this collective feeling such as fear of watchwords, of speeches and of the left party symbols; third, the Workers’ Party attracted experienced militants and enemies of the regime and then, formed new militants, fourth, the movement which had generated PT (Workers’ Party) brought to Espirito Santo State national issues such as amnesty, re-democratization, struggle for better salaries and work conditions besides reproducing great movements like strikes and campaigns; fifth, PT was a kind of agglutinant for several and different political oppositions to the military regime.